Here's the question you clicked on:
waheguru
How do I convert y = 2/3 x - 7 to standard ax + by +c = 0 form
*more so I do i get the = 0 part...??
Since you have a denominator of 3, first multiply both sides by 3. Then add or subtract the terms on the right side to move them to the left side.
y = 2/3 x - 7 Multiply both sides by 3: (3)y = (3)(2/3 x - 7) What do you get? Remember to distribute the 3 on the right side.
what do i do from here?
Now since you want everything on the left side, subtract 2x from both sides, and add 21 to both sides.
can you please show the following steps
3y = 2x - 21 -2x + 21 -2x + 21 -------------------------- -2x + 3y + 21 = 0 If you don't like to have a negative sign at the beginning (with the x term), you can multiply both sides by -1 and get 2x - 3y - 21 = 0
but i also saw a formula in standard from as 2x-3y = 12. would this be condisered stard from